The Relationship Between Body Mass Index and Lung Vital Capacity in FK UNJANI Students in the 2021-2022 Batch Year - Apen Afgani Ridwan; Masroor Fitru Robbi; Yuke Ireka (Jurnal EduHealth, 2026)
Body Mass Index (BMI) is a nutritional status indicator that can affect lung function, including vital lung capacity (VLC). Increased BMI may reduce lung capacity due to increased airway resistance, decreased lung tissue elasticity, and fat accumulation in the thoracic and abdominal walls, which restricts diaphragmatic movement. Conversely, low BMI may contribute to reduced vital lung capacity due to decreased respiratory muscle mass, which plays a crucial role in ventilation. This study aimed to analyze the relationship between BMI and vital lung capacity among FK UNJANI students. A cross-sectional study design was used with a total of 37 randomly selected students. BMI was calculated based on weight and height, while vital lung capacity was measured using a spirometer. Data were analyzed using the Pearson correlation test with a significance level of p<0.05. The analysis showed a very weak correlation between BMI and vital lung capacity (r = 0.077) and was not statistically significant (p = 0.652). No meaningful relationship was found between BMI and vital lung capacity in this study sample. Besides BMI, other factors such as body composition (excess fat restricts lung expansion, while muscle mass supports ventilation), exercise habits (enhancing respiratory muscle strength), posture (poor posture can limit lung expansion), and environmental factors (pollutant exposure and allergies impair lung function) may have a greater impact on lung capacity. Further studies with larger sample sizes and more diverse variables are needed for more accurate and generalizable findings.